Handbook of ecotoxicology (Blackwell Science, 1993)
The book provides a readily accessible, yet critical collection of information on ecotoxicological practice and results. Information on the prediction and monitoring of the impact of chemicals derived from human activities on natural ecosystems is spread far and wide